Discovering School principals’ Servant Leadership Practices in Serving Teachers - Jeremiah Khoarane (Indonesian Educational Research Journal, 2023)
There is an interesting issue that concerns leadership in 21 century that is faced with the 4th industrial revolution on leadership. This paper aimed to discover school principals’ practices of servant leadership in serving teachers. The study engaged servant leadership and Cultural Historical Activity Theory (CHAT) as theoretical frameworks. Servant leadership was used to interpret the practices of the school principals, while CHAT was used to identify and explain the findings in terms of culture and context. Two schools were chosen; both are owned by the public and found in the rural area of Maseru. This paper is located within an interpretive paradigm and adopts a qualitative approach. The study engaged focus groups, interviews, and observation. There were two focus groups, one from each school. There were 8 members in each focus group. The interview was done with the school principals of the two schools in Lesotho. The findings revealed that school principals practiced servant leadership. One core business of servant leadership is to serve. Teachers were served by reducing conflicts, facilitating the decentralization at school, promoting information sharing in schools; augmenting teacher commitment boosting job satisfaction and retention of teachers, creating a pleasant working climate, and developing teamwork.